An Analysis of the Singing Method in Children's Religious and Moral Values Learning in Islamic Education - loka, novita; Ichsan, Ichsan (Universitas Islam Negeri Raden Intan Lampung, 2022)
The learning method often used in preschool institutions is the lecturing method or the question and answer method. If the methods are continuously applied, children's learning motivation can decrease, especially in religious and moral values learning within the scope of Islamic education. A method that can increase children's motivation and development is needed, such as the singing method. The singing method can improve the development of children's religious and moral values. This research is field research with a descriptive quantitative approach. The researchers collected the data using observation, interviews, and documentation. The data were analyzed using the observation results' average or mean. The analysis found that the singing method could increase the development of children's religious and moral values. So it can be concluded, the singing method can be used effectively if applied properly because it is fun and can increase learning motivation. This method can be an alternative for teachers in developing religious and moral values.